(untitled) (Research, Society and Development, 2022)
Introduction: The literature has shown an increase in the prevalence of children with allergy to cow’s milk protein (APLV) and their treatment consists of this food and its dietary derivatives and its replacement by formulas based on isolated soy protein or formulas hydrolyzed. Objective: To evaluate the effects of using nutritional formulas in children with APLV. Methodology: The search and selection of articles followed the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), using the keywords: “milk hypersensitivity”,” food hypersensitivity, hydrolyzed”, “vegetable protein”, “vegetable protein”, “soy bean proteins” in combination or alone, in Pubmed, Scopus and Science direct databases. Results: Nine articles were included, including six clinical trials, a cohort study, an observational study and a multicenter study. Were tested: extensively hydrolyzed protein formula, amino acid-based formula and soy-based formula. In 3 studies, extensively hydrolyzed protein and amino acid formulas were associated with probiotics Lactobacillus rhamnosus. and there were 2 studies associated with symbiotics. Conclusion: All types of formulas analyzed contributed to improvement in symptoms related to APLV, with the best results observed for formulas with probiotics. However, further studies are needed to assess the effects of added probiotics in nutritional formulas for the treatment of APLV, its potential needs to be better evaluated, especially in long-term studies.